If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4 + x) + -1(1 + -7x) = -54 (4 * 4 + x * 4) + -1(1 + -7x) = -54 (16 + 4x) + -1(1 + -7x) = -54 16 + 4x + (1 * -1 + -7x * -1) = -54 16 + 4x + (-1 + 7x) = -54 Reorder the terms: 16 + -1 + 4x + 7x = -54 Combine like terms: 16 + -1 = 15 15 + 4x + 7x = -54 Combine like terms: 4x + 7x = 11x 15 + 11x = -54 Solving 15 + 11x = -54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 11x = -54 + -15 Combine like terms: 15 + -15 = 0 0 + 11x = -54 + -15 11x = -54 + -15 Combine like terms: -54 + -15 = -69 11x = -69 Divide each side by '11'. x = -6.272727273 Simplifying x = -6.272727273
| x^3-2*x^2+18*x+28=0 | | -2.6x+18=2.4x+22 | | 3y+0=-15 | | 9x+3-4x=8 | | e^5x=23 | | -2(j+5)+6=4(j+2) | | -4r-2r-6-4= | | -3-(-17)=-4 | | f(x)=8x-x^2 | | 1k-8=-10 | | 17x+2=25x-3 | | 1.5+x=7 | | 3.75c+1.125=10.25 | | 4(3z+12)-11=12z+37 | | 2x+9-.74x+2.24= | | 5(2x-1)-9= | | 5(2x-3)=21+4x | | 6m=2n+r | | 8x+3=180 | | x=-2.1538 | | -12+8m=-2m+48 | | 8-3(2x-1)=4(3-2x) | | 7/6-a-4/9=-a | | 15+17y=14+9y | | 8-.67x=72 | | X+8y=10 | | (2x+6)+(2x-6)+x=180 | | 8+7x=12+5x | | -4y-0=8 | | 9x-y=40 | | 2(m-7)+4m=7m+8-m | | x*2=8.3 |